El libro sensorial interactivo como estrategia para fortalecer la comprensión de ciencias naturales en estudiantes de tercero de EGB en la Escuela Básica “Alejandro Sergio Bermeo”, cantón Chimbo, provincia Bolívar, durante el año lectivo 2024-2025 - Romero Verdezoto, Brandon Nahin (2025)
This research project focuses on innovating the teaching-learning process through the design and implementation of an interactive sensory book as a strategy for understanding Natural Sciences. This approach stems from the need to respond to students' real learning needs with visual and tactical resources that integrate technology to encourage students to understand content in a more playful, dynamic, and participatory way. The challenges that exist when teaching Natural Sciences are evident. The lack of strategies prevents students from understanding complex topics. Therefore, it is essential to use effective strategies that facilitate the learning process and increase students' motivation to learn. The methodology employed involves a mixed-method approach, allowing for the collection of data, experiences, and perceptions about the use of an interactive sensory book as a strategy for understanding natural sciences. This led to the development of a proposal for the implementation of a sensory book consisting of innovative activities that promote innovative learning. In conclusion, it is determined that an interactive sensory book does not replace existing methodologies but rather complements them with technological tools that strengthen the teaching and learning process in the classroom. This aims to transform the way in which sciences are taught, as it makes natural science content more understandable, and appropriate for different educational levels.